COMMUNITY OF CULTIVABLE ENDOPHYTIC FUNGI OF CASSAVA Manihot esculenta CRANTZ - Viana Diniz, Fernanda; Martins Pereira, Veluma; de Freitas Lopes , Nathalia; Medeiros Vasconcelos, Janaína; Vasconcelos de Araujo, Atilon; Maia Carvalho, Clarice (DESAFIOS - Revista Interdisciplinar da Universidade Federal do Tocantins, 2022)
The objective of this work was to characterize the community of endophytic fungi of cassava Manihot esculenta cultivated in the state of Acre, Brazil. For that, M. esculenta root, stem and leaf were collected, washed and disinfected by immersion in 70% ethanol (1 min), sodium hypochlorite 2% (5 min), 70% alcohol (30 sec) and washing in water sterile distilled (1 min) three times. The samples were fragmented and inoculated in BDA and Oat culture media and incubated at 28 º C for 30 days. The isolated fungi were characterized by morphology and grouped into morphospecies. There was isolated a total of 39 endophytic fungi M. esculenta, 19 (48.7%) of stem 13 (33.3%) of leaf and 7 (18%) root. On culture medium, 23 (59%) fungi were isolated in BDA medium and 16 (41%) in Oat medium. Eight fungal genera were identified, Penicillium and Phomopsis the most frequent, with 30.8% relative frequency each, and Fusarium (10.2%) Aspergillus (5.1%), Guignardia (5.1%), Acremonium (2.6%), Colletotrichum (2.6%), Phoma (2.63%), and unidentified (10.2%). M. esculenta showed dominance by fungi of the genera Penicillium and Phomopsis. This is the first study report of the endophytic fungi community of Manihot esculenta.